Edição procedimental de terrenos virtuais utilizando curvas de Bézier 3D de baixo grau em GPU - Nascimento, Bruno Torres do (2020)
The procedural generation of virtual terrains from geospatial data is used in several cate- gories of applications, such as virtual simulators, games, and visualization of GIS data, and often demands the visual integration of roads, rivers, and other terrain features. This work presents a procedural technique for carving paths on virtual terrains generated from Digital Elevation Models (DEM). A path is a feature on the terrain with a well-defined route, such as a road or river. The paths are loaded from vector data and converted from polylines to 3D cubic Bézier curves with C2 continuity and smoothness parameterization. Then, the cubic curves are divided and transformed into quadratic curves and sent to the GPU where our technique processes the entire heightmap in parallel, calculating the displacements to cre- ate excavations and embankments on the terrain along the paths. Our technique employs a spatial hash using the bounding boxes of the curves to reduce calculations on the GPU. The approach of using quadratic curves allows the calculations of point-to-curve distances to be carried out analytically, promoting a substantial improvement in performance when compared to numerical approaches, and allowing reaching times compatible with real-time execution. In addition, the use of a set of carving parameters allows the user to control the dimensions and profile of the paths sculpted in the terrain, changing the width, the lateral inclination, and the smoothing distance, producing smooth and natural-looking paths.